2021
DOI: 10.1039/d1dt00436k
|View full text |Cite
|
Sign up to set email alerts
|

Meta-studtite stability in aqueous solutions. Impact of HCO3, H2O2 and ionizing radiation on dissolution and speciation

Abstract: The two uranyl peroxides meta-studtite and studtite exist in nature and can form as alteration phases on the surface of spent nuclear fuel upon water intrusion in a geological repository....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…Under these conditions, the consumption of H 2 O 2 was found to follow first-order kinetics during the initial phase of the reaction. At higher conversion, the formation of colloidally stable studtite particles (pure water) and uranyl-peroxo-carbonate complexes start to influence the analysis as well as the reaction dynamics of the system. The resulting first-order rate constants are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Under these conditions, the consumption of H 2 O 2 was found to follow first-order kinetics during the initial phase of the reaction. At higher conversion, the formation of colloidally stable studtite particles (pure water) and uranyl-peroxo-carbonate complexes start to influence the analysis as well as the reaction dynamics of the system. The resulting first-order rate constants are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that UO 2 2+ can form complexes and clusters with a wide variety of Lewis base ligands such as water, carbonate, hydroxide, peroxide, and halides. Vallet et al reported the affinity of the ligands to increase in the order H 2 O < Cl – < F – < OH – < CO 3 2– < O 2 2– based on quantum chemical calculations. UO 2 2+ binding to O 2 2– in aqueous solution at low concentrations of competing ligands can precipitate as studtite at ambient temperature and as meta-studtite at temperatures higher than 70 °C. , Studtite and meta-studtite are the only two uranyl peroxide minerals found in nature, and they have also been found on the surface of spent nuclear fuel, on the “lava” of the Chernobyl disaster, and on damaged reactor cores after the Fukushima nuclear accident …”
Section: Introductionmentioning
confidence: 99%
“…In a very recent work, the H 2 O 2 -induced oxidative dissolution of UO 2 in saline aqueous solutions was partly explained by the formation of ternary uranyl–peroxo–chloro and uranyl–peroxo–bromo complexes . The existence of ternary uranyl–peroxo complexes is well established in carbonate-containing solutions, where uranyl–peroxo–carbonate complexes are formed and in alkaline solutions where uranyl–peroxo–hydroxo complexes can be formed. , Previous studies have shown that studtite and meta-studtite can dissolve and transform into the ternary complexes under these conditions . Given the indirect indication of the existence of ternary uranyl–peroxo–halo complexes and their potential importance in understanding spent nuclear fuel dissolution in saline solutions, it is essential to investigate their possible existence and properties using more direct methods.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the concentrations of H 2 O 2 and O 2 •– /OOH • produced upon irradiation of aerated solutions was about 10 4 times higher in comparison to inert gas analogues due to the reactivity of e – aq and OH • toward molecular oxygen . Reactive oxygen species (e.g., H 2 O 2 ) can interact with the surface of nuclear waste, oxidizing U IV to the uranyl cation (U VI O 2 2+ ), which opens up a major pathway to the formation of uranyl peroxide alteration phasesstudtite ([UO 2 (O 2 )­(H 2 O) 2 ]·2H 2 O) and metastudtite ([UO 2 (O 2 )­(H 2 O) 2 ]). , Both mineral phases have been shown to solubilize at slightly basic pH values to form uranyl peroxide closed-cage clusters and have the potential to mobilizing U VI into the surrounding aqueous environment. , Additionally, upon the γ-irradiation of suspensions containing studtite and metastudtite in the presence of HCO 3 – anions, the rapid dissolution of both minerals was observe,d resulting in uranyl peroxo-carbonate compounds …”
Section: Introductionmentioning
confidence: 99%
“…24,25 Additionally, upon the γ-irradiation of suspensions containing studtite and metastudtite in the presence of HCO 3 − anions, the rapid dissolution of both minerals was observe,d resulting in uranyl peroxo-carbonate compounds. 26 The formation of hydrogen peroxide in aqueous solution relies on the reactivity of reactive intermediates, such as the recombination of hydroxyl OH • radicals in a major pathway, as well as hydrogen radical H • capture by OOH • in a minor pathway, and there is initial evidence that the OOH • species may bind and stabilize through interactions with the U VI O 2 2+ cation. We have recently shown that O 2…”
Section: Introductionmentioning
confidence: 99%